Overexpression of a Functional Vicia sativa PCS1 Homolog Increases Cadmium Tolerance and Phytochelatins Synthesis in Arabidopsis - Zhang, Xingxing; Rui, Haiyun; Zhang, Fenqin; Hu, Zhubing; Xia, Yan; Shen, Zhenguo (Frontiers in Plant Science, 2018)
Phytochelatins (PCs) catalyzed by phytochelatin synthases (PCS) is important for the detoxification of metals in plants and other living organisms. In this study, we isolated a PCS gene (VsPCS1) from Vicia sativa and investigated its role in regulating cadmium (Cd) tolerance. Expression of VsPCS1 was induced in roots of V. sativa under Cd stress. Analysis of subcellular localization showed that VsPCS1 was localized in the cytoplasm of mesophyll protoplasts of V. sativa. Overexpression of VsPCS1 (35S::VPS1) in Arabidopsis thaliana could complement the defects of Cd tolerance of AtPCS1-deficent mutant (atpcs1). Compared with atpcs1 mutants, 35S::VsPCS1/atpcs1 transgenic plants significantly lowered Cd-fluorescence intensity in mesophyll cytoplasm, accompanied with enhanced Cd-fluorescence intensity in the vacuoles, demonstrating that the increased Cd tolerance may be attributed to the increased PC-based sequestration of Cd into the vacuole. Furthermore, overproducing VsPCS1 could enhance the Cd tolerance of wild-type Arabidopsis (WT), but have no effect on Cd accumulation and distribution, showing the same level of Cd-fluorescence intensity between 35S::VsPCS1 and wild-type plants. Further analysis indicated this increased tolerance in WT was possibly due to the increased PCs-chelated Cd in cytosol. Taken together, a functional PCS1 homolog from V. sativa was identified, which hold a strong catalyzed property for the synthesis of high-order PCs that retained Cd in the cytosol rather the vacuole. These findings enrich the original model of Cd detoxification mediated by PCS in higher plants.